2014
DOI: 10.1111/codi.12763
|View full text |Cite|
|
Sign up to set email alerts
|

Laparoscopic ventral mesh rectopexy in male patients with internal or external rectal prolapse

Abstract: LVMR is an effective treatment for external and symptomatic internal rectal prolapse in men, leading to significant improvement in QoL and function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 25 publications
0
25
0
Order By: Relevance
“…All patients had internal rectal prolapse (IRP) diagnosed clinically, by defaecography and/or by examination under anaesthesia. Eight studies , including 971 patients, reported the presence of a concomitant anterior rectocele in 671 (69.1%) patients. Ten studies, which included 1158 patients, classified rectoanal intussusception according to the Oxford grading system as Grade I–II in 50 (4.4%) patients and Grade III–V in 1108 (95.6%).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…All patients had internal rectal prolapse (IRP) diagnosed clinically, by defaecography and/or by examination under anaesthesia. Eight studies , including 971 patients, reported the presence of a concomitant anterior rectocele in 671 (69.1%) patients. Ten studies, which included 1158 patients, classified rectoanal intussusception according to the Oxford grading system as Grade I–II in 50 (4.4%) patients and Grade III–V in 1108 (95.6%).…”
Section: Resultsmentioning
confidence: 99%
“…The median operation time was 110 (60–198) min in five studies. and the median length of hospital stay was 2 (1–7) days in nine studies. The median duration of follow‐up was 19 (12–76) months.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These ligaments contain nerves to the rectal wall and the resultant denervation may be the cause. In the process of developing alternative resuspending procedures, surgeons have attempted to limit the effect of the foreign material by using sutures only [5], added a resection of the sigmoid colon to the rectopexy [6][7][8] or more recently, limiting the dissection of the rectum to the ventral surface by supporting the rectum with mesh [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. In addition, laparoscopy has become the favoured approach procedurally, not only allowing a more rapid recovery but also easing access to, and visibility in the pelvis.…”
Section: Introduction Background and Procedural Variationsmentioning
confidence: 99%